Roads do not increase carrion use by a vertebrate scavenging community. Issue 1 (December 2018) - Hill, Jacob; DeVault, Travis; Beasley, James; Rhodes, Olin; Belant, Jerrold
Abstract Wildlife-vehicle collisions introduce a considerable amount of carrion into the environment, but scavenger use of this resource has not been extensively investigated. Scavengers may use roads for reliable foraging opportunities, but might also use roads for other purposes and encounter carrion opportunistically. We examined scavenging of carrion along linear features by placing 52 rabbit carcasses in each of three treatments in forested habitat during winter (Dec 2016-Mar 2017) in South Carolina, USA: roads, power line clearings (linear feature with fewer carcasses than roads due to lack of road kill), and forest interior. We used motion-activated cameras to compare arrival times and presence of vertebrate scavengers among treatments. There was no difference in proportion of carcasses scavenged or scavenger arrival time across treatments. No species arrived at roads quicker than other treatments. Turkey vultures (Cathartes aura ) and coyotes (Canis latrans ) scavenged equally across treatments, whereas gray foxes (Urocyon cinereoargenteus ) scavenged along roads and power lines, but not in forests. We suggest that scavenger use of carrion near roads at this location during winter relates to factors other than carrion availability. Because some scavengers readily consumed carrion on roads, this resource has the potential to influence the ecology of these species.